Aspects of working Ukrainian citizens in Hungary - Pakurár, Miklós; Cehla, Béla; Oláh, Judit; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2013)
The primary focus of the joint survey, by the National Employment Foundation (OFA) and the researchers of the University of Debrecen in 2009, was to identify the employment characteristics of Ukrainian citizens in Hungary in relation to their impact on the labour market. Our research activities implied the analysis of existing data, relevant scientific literature and a survey questionnaire. For all the target groups, we were guided by the principle of representativity. Statistical analyses and the survey questionnaire were supplemented by indepth interviews. Our research findings are instrumental in simplifying the administration of the Foreign Affairs Police, the process of issuing work permits for foreign employees and their access to employment. The responses given by employees revealed that access to employment in Hungary posed several administrative and official problems for both Hungarian and Ukrainian citizens. Moreover, Ukrainian employees felt a kind of negative discrimination regarding their wages and the conditions of employment as compared to Hungarian employees and they sought remedy from Hungarian official bodies for this problem. The authors hope to call the attention of competent authorities to structural problems and loopholes in the employment of foreign citizens. If these are corrected, it will not only improve employment conditions for foreign workers, but for Hungarian ones as well.